Development of Video Learning Media in Islamic Religious Education Subjects Theory Material on the Entry of Islam to Indonesia - Suwartiningsih, Suwartiningsih; Besari, Anam (STAI MA'ARIF MAGETAN, INDONESIA, 2024)
This research is practically useful for teachers to create active and enjoyable learning in class, as well as used by students as a learning tool at home and the usefulness of this research for researchers is to add experience and also channel hobbies into education. While the purpose of this study is to develop video media that is valid, effective and also practical in the subject of Islamic Religious Education on the material of the Theory of the Entry of Islam into Indonesia at SMK Negeri 1 Kartoharjo Magetan Regency. This type of research is R & D (Research and Development), which is research and development. Data collection techniques are divided into 3 namely, validation sheets, questionnaire sheets and also observation sheets. The research subject is class XI at SMK Negeri 1 Kartoharjo Magetan Regency. The data source is primary data. The result of the research is a learning video of Islamic Religious Education subject matter Theory of The theory of the entry of Islam into Indonesia has been validated, tested for effectiveness and practicality. The validity of this research product by media experts and material experts is 86%. The effectiveness of this research product based on post test trials made an increase in student learning outcomes whose scores were completed by 82, 75%. The practicality of the learning video product based on the teacher observation sheet applying it was 96.66%.